2020
DOI: 10.1155/2020/6053065
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Pulsed Xenon Ultraviolet Disinfection Device for Real-Time Air Disinfection in Ambulances

Abstract: Objectives. We have developed a pulsed xenon ultraviolet light-based real-time air disinfection system with rapid and effective disinfection by using high-intensity pulse germicidal UV. Disinfection of the ambulance's environment is critical in the prevention of infectious cross contamination. Methods. In this study, a pulsed xenon ultraviolet light-based air disinfection system was established for real-time air disinfection in ambulances. In this system, a pulsed xenon ultraviolet (PX-UV) was used to generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…It is sub-divided into UV-A (ultraviolet A) with wavelengths from 320 to 400nm which is capable of causing changes in the skin causing aging; UV-B (ultraviolet B), with wavelengths from 280 to 320nm, which causes genetic mutations and can lead to skin cancer [32]; and UV-C (ultraviolet C) with wavelengths from 200 to 280nm [32][33][34], which is the most harmful band, being the germicidal band, interacting directly with the genetic material of the microorganisms, inactivating them and interrupting their contagion cycle [32]. UV irradiation has been proposed as a method of terminal disinfection in a variety of applications such as air, water, and contaminated surfaces [26,28,29,[35][36][37][38], and it can also be generated sin different ways, the most traditional being the mercury gas lamp. Currently, new technologies are being used without the presence of mercury, such as xenon pulsed light (200 to 300nm) that is emitted in a short duration, high pulse intensity, requiring a shorter exposure time [1,36,39], and the technology based on LED (light emitting diode), which proposes the use of smaller equipment, with fast start up time and equal efficiency, however, with low energy load [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is sub-divided into UV-A (ultraviolet A) with wavelengths from 320 to 400nm which is capable of causing changes in the skin causing aging; UV-B (ultraviolet B), with wavelengths from 280 to 320nm, which causes genetic mutations and can lead to skin cancer [32]; and UV-C (ultraviolet C) with wavelengths from 200 to 280nm [32][33][34], which is the most harmful band, being the germicidal band, interacting directly with the genetic material of the microorganisms, inactivating them and interrupting their contagion cycle [32]. UV irradiation has been proposed as a method of terminal disinfection in a variety of applications such as air, water, and contaminated surfaces [26,28,29,[35][36][37][38], and it can also be generated sin different ways, the most traditional being the mercury gas lamp. Currently, new technologies are being used without the presence of mercury, such as xenon pulsed light (200 to 300nm) that is emitted in a short duration, high pulse intensity, requiring a shorter exposure time [1,36,39], and the technology based on LED (light emitting diode), which proposes the use of smaller equipment, with fast start up time and equal efficiency, however, with low energy load [40].…”
Section: Discussionmentioning
confidence: 99%
“…UV irradiation has been proposed as a method of terminal disinfection in a variety of applications such as air, water, and contaminated surfaces [26,28,29,[35][36][37][38], and it can also be generated sin different ways, the most traditional being the mercury gas lamp. Currently, new technologies are being used without the presence of mercury, such as xenon pulsed light (200 to 300nm) that is emitted in a short duration, high pulse intensity, requiring a shorter exposure time [1,36,39], and the technology based on LED (light emitting diode), which proposes the use of smaller equipment, with fast start up time and equal efficiency, however, with low energy load [40]. Regardless of the source of ultraviolet light, the most effective wavelength is 254nm [36,[39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The most common feature of these tests was the use of two cycles of disinfection of five minutes. While PL has not been tested to disinfect contaminated air in hospital rooms, it should be able to do it according to the evidence collected when testing the disinfection of air in ambulances [ 85 ].…”
Section: Use In Health Care Facilitiesmentioning
confidence: 99%
“…On the other hand, Chen et al [ 81 ] and Li et al [ 87 ] studied not only the disinfection of various surfaces of different rooms, but also verified the effect of PL on air disinfection, since they achieved a log reduction of one to full reduction of the biological burden [ 81 , 87 ]. Furthermore, Song et al [ 85 ] suspended Escherichia coli and Staphylococcus albus in a liquid that was aerosolized in two security booths, which were later treated with a PL device during 30 min. After the encouraging results obtained in the laboratory model, the same protocol was adapted to ambulances that had been used throughout a workday increasing the treatment time to 60 min.…”
Section: Use In Health Care Facilitiesmentioning
confidence: 99%
“…They have shown that pulsed xenon and mercury lamps have the same effectiveness at relatively short exposure time, about 10 min. Song et al (2020) have used continuous and pulsed xenon UV to inactivate microorganisms in ambulances. They have reported that the device does not need to use chemical agents and reduce 90% of E. coli, Staphylococcus albus, and environmental pathogens in 30 min.…”
Section: Disinfection Unitmentioning
confidence: 99%